2022
DOI: 10.3390/pr10091889
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Osmosis Modeling Study of Lead and Arsenic Removal from Drinking Water in Tarija and La Paz, Bolivia

Abstract: An investigation of primary water sources in two Bolivian basins identified the presence of heavy metals toxic to health that exceeded the permissible limits for drinking water. Lead deposited in the San Jacinto and Huacata–Tarija reservoirs within the Guadalquivir basin and arsenic in the Milluni–La Paz basin were identified. The work studies reverse osmosis (RO) to remove Pb and As. The main contribution of this research is the development and construction of a mathematical model based on the Spiegler–Kedem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The Kedem model describes the physical behavior of the reverse osmosis membrane. In experiments on a laboratory scale [42], it was shown that at low pressures, 5 to 10 bar, an efficiency in the removal of heavy metals of up to 99% is achieved.…”
Section: Resultsmentioning
confidence: 99%
“…The Kedem model describes the physical behavior of the reverse osmosis membrane. In experiments on a laboratory scale [42], it was shown that at low pressures, 5 to 10 bar, an efficiency in the removal of heavy metals of up to 99% is achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Bolivia has experienced significant population growth and unorganized development, which has led to a growing and sustained process of water contamination in various areas of the country. Similarly, several water sources in the Municipality of Tarija, Bolivia, present toxic contaminants, such as heavy metals, which represent a risk to the public health of the population [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Political, social, and cultural differences hinder the implementation of public policies and the execution of investment projects. Recent investigations carried out in Tarija and La Paz, Bolivia [16], demonstrate the effectiveness of the removal of toxic contaminants present in drinking water through reverse osmosis. The results show that reverse osmosis can be implemented at low operating pressures, demonstrating significant sustainability in terms of energy and economic efficiency [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, an adjustment was made to the temperature factor that was based on the Arrhenius model to prevent this factor from influencing the response variables. Several mathematical models have described the mass transfer and hydrodynamic permeability in RO systems [58]. Using a mathematical model that expresses the performance of the RO process is a mechanism that could help to reduce operating costs [59], but it is also necessary to complement the study of the process through statistical analysis, which focuses on the outputs and inputs to know the behavior of the RO and to be able to optimize it [50].…”
mentioning
confidence: 99%